Establishing SPV for power projects in Asia: an analysis of critical financial and legal factors - Chowdhury, Abu Naser; Chen, Po-Han; Tiong, Robert Lee Kong (Journal of Business Economics and Management, 2012)
One of the main reasons for the success of Public Private Partnership (PPP) projects is the creation of separate commercial venture named ‘Special Purpose Vehicle’ (SPV). SPV provides a good framework for raising funds, linking participants legally and assuring supply, production and marketing of products. SPV brings together various parties like lenders, financial institutions, public sector and export credit agencies, guarantors, suppliers and off-takers. There is often a lack of precedents to identify factors of SPV and the process is further hampered by undeveloped financial and legal structures of a country. A number of factors need to be considered before setting up of SPV for PPP projects. A questionnaire survey was thus conducted to explore the most important factors in setting up SPV for PPP power projects from a wide range of personnel involved in the PPP processes in Asia. The objective of this paper is to investigate the current practice of setting up SPV and associated legal and financial impacts onto it. Analysis of the response data reflects experts’ opinion in identifying the influential factors and the choices in setting up SPV for PPP power projects in Asia. The findings of the paper would help the public sector in implementing PPP power policy development and private sector sponsors in managing the projects.